Siblings in the Unconscious and Psychopathology : Womb Fantasies, Claustrophobias, Fear of Pregnancy, Murderous Rage, Animal Symbolism, Christmas and Easter "Neuroses", and Twinnings or Identifications with Sisters and Brothers. - Ast, Gabriele (Karnac Books, 2014)
Annotation